Efektivitas Daun Gamal (Gliricidia Sepium) Sebagai Pestisida Nabati Pengendalian Uret (Lepidiota Stigma): Efektivitas Daun Gamal (Gliricidia Sepium) Sebagai Pestisida Nabati Pengendalian Uret (Lepidiota Stigma) - Retno Muningsih; Indi Afaita Syakira; Toyip (JURNAL ILMIAH AGRINECA, 2026)
The continuous use of chemical insecticides to control white grubs (Lepidiota stigma F.) in sugarcane fields may negatively affect the environment, so botanical alternatives are needed. This study evaluated gamal leaves (Gliricidia sepium) as a botanical pesticide for controlling white grubs. The research was conducted at the TEFA, Politeknik LPP Yogyakarta, and the Integrated Research and Testing Laboratory (LPPT), Universitas Gadjah Mada. A Randomized Block Design was used with gamal leaf doses of 0, 250, 500, 750, and 1000 g, and comparison treatments using chemical insecticides with the active ingredients fipronil and carbofuran 3%. The observed parameters were live grubs, dead grubs, infected grubs, and infection rate. Gamal leaf treatments produced different responses. Live grubs ranged from 2 to 3 individuals, while dead grubs ranged from 7 to 8 individuals. The highest infected grubs in gamal treatments occurred at 250 g and 750 g, with an infection rate of 4. These findings indicate that gamal leaves have potential as a botanical pesticide for white grub control in sugarcane fields. Keyword: Gamal Leaves, Gliricidia sepium, Botanical Pesticide, White Grub, Infection Rate